Performance Estimation of Heat Exchanger Operates By Evaporative Cooling Manner - Mohammed, Imaad Sedeeq; Juaad, Salah Karem (Al-Khwarizmi Engineering Journal, 2019)
In this study the design and installation of evaporative air cooler was carried out using completely outdoor air (fresh air) according to two stage evaporative cooling principle. The laboratory equipment was installed by designing and manufacturing a cross flow plate heat exchanger, where aluminum plates used for this purpose with dimensions (50 × 30 × 40 cm). The surfaces of heat exchanger were covered by sawdust from wetted channels side, to increase the percentage of wetting these surfaces and hence improve the performance and efficiency of air cooler.        An experimental study was carried out to estimate the performance of cooling system, where some of the dominant effective parameters were studied like air flow rate and flow rate and effect the static pressure drop of air and the heat transfer of performance .Air flow rate was ranged between (142.90 to 1461.50 m3 / hr) and water flow rate was varied from (144 L / hr) to (1050 L / hr).        The experimental results showed that the optimum flow rate of air prepared by the air cooler is (824.7 m3 / hr), As it to be seen from the study that treating the heat exchanger surfaces by sawdust improves the air cooler efficiency about (10 %), but in the other hand leads to increase the static pressure drop in proportion (21%) approximately, and hence increase consumed power about (9 %).The results also show the air cooler can not be used in regions that have moisture content accedes (11.90 g moisture/kg dry air).